Pengaruh Kecerdasan Emosional Terhadap Peyesuaian Diri Para Calon Biarawati - Oeleu, Demetriana; Barus, Debi Angelina Br (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This experimental research aims to find out the impact of emotional intelligence on self-adaptation in future nuns. The subject is the candidate nun of the Flos Carmel Monastery Community in the Sikka district, which consists of 111 female monks aged 18-22. The measurement used is a self-adjustment scale. As for data collection techniques using purposive sampling with criteria. Data analysis method using paired sample test with the help of SPSS for windows 16.0. The analysis results showed there was a change in self-adjustment after given the tablet with a significant scale of 0,000. So there's an increase in self-adaptation in the future nun Flos Carmeli.